Associations of Acid Suppressive Therapy With Cardiac Mortality in Heart Failure Patients. Issue 5 (May 2017) - Yoshihisa, Akiomi; Takiguchi, Mai; Kanno, Yuki; Sato, Akihiko; Yokokawa, Tetsuro; Miura, Shunsuke; Abe, Satoshi; Misaka, Tomofumi; Sato, Takamasa; Suzuki, Satoshi; Oikawa, Masayoshi; Kobayashi, Atsushi; et al.
Abstract : Background: It has been recently reported that histamine H2 receptor antagonists (H2RAs) are associated with impairment of ventricular remodeling and incident heart failure. In addition, favorable pleiotropic effects and adverse effects of proton pump inhibitors (PPIs) on cardiovascular disease have also been reported. We examined the associations of acid suppressive therapy using H2RAs or PPIs with cardiac mortality in patients with heart failure. Methods and Results: In total, 1191 consecutive heart failure patients were divided into 3 groups: a non–acid suppressive therapy group (n=363), an H2RA group (n=164), and a PPI group (n=664). In the follow‐up period (mean 995 days), 169 cardiac deaths occurred. In the Kaplan–Meier analysis, cardiac mortality was significantly lower in the PPI group than in the H2RA and non–acid suppressive therapy groups (11.0% versus 21.3% and 16.8%, respectively; log‐rank P =0.004). In the multivariable Cox proportional hazards analysis, use of PPIs, but not H2RAs, was found to be an independent predictor of cardiac mortality (PPIs: hazard ratio 0.488, P =0.002; H2RAs: hazard ratio 0.855, P =0.579). The propensity‐matched 1:1 cohort was assessed based on propensity score (H2RAs, n=164; PPIs, n=164). Cardiac mortality was significantly lower in the PPI group than in the H2RA group in the postmatched cohort (log‐rank P =0.025). In the Cox proportional hazards analysis, the use of PPIs was a predictor of cardiac mortality in the postmatched cohort (hazard ratio 0.528, P =0.028). Conclusions: PPIs may be associated with better outcome in patients with heart failure.